Daily life of women in medieval Europe - Tuten, Belle S. (The Greenwood Press daily life through history series, 2022)
Cover -- Title Page -- Copyright -- Contents -- Preface -- Introduction -- Chronology -- 1. Marriage and Sexuality -- Late Antique and Early Medieval Marriage -- Roman Marriage -- Germanic Marriage -- Age at First Marriage -- The Christian Influence on Early Medieval Marriage -- Sex in Marriage-Fourth Through Eleventh Centuries -- Concubinage and Polygyny -- High Medieval Marriage and Sexuality -- Sex in Marriage-Twelfth to Fifteenth Centuries -- Positive and Negative Views of Sex -- Positive and Negative Views of Marriage and Women -- Jewish Marriage and Sexuality -- Rape and Sexual Violence -- Domestic Abuse -- Conclusion -- 2. Childbirth, Child Rearing, and the Life Cycle -- Understanding the Female Body -- Pregnancy -- Childbirth -- Birth Attendants and Midwives -- Contraception, Abortion, and Infanticide -- Illegitimacy and Abandonment -- The Ages of Man -- Stages of Life: The Family -- Stages of Life: Infancy -- Stages of Life: Adolescence -- Stages of Life: Adulthood -- Stages of Life: Widowhood -- Stages of Life: Old Age -- Stages of Life: A Good Death -- Conclusion -- 3. Working Women -- Living and Working in the Countryside: Serfs and Peasants -- Everyday Food -- Upper-Class Food and Feasts -- Cloth Production -- Town Work in the Middle Ages -- Creating and Transmitting Knowledge: Book Production -- Caregiving and Healing -- Conclusion -- 4. Noble Women -- Marriages and Children -- Dowry, Dower, and Inheritance -- Royal Power and Regency -- Conduct of an Aristocratic Lady: Ideals -- Daily Life for Upper-Class Women -- Leisure Time -- Conclusion -- 5. Religion and the Church -- Daily Religious Practice -- Finances and Endowments -- New and Reformed Religious Orders -- Lay Piety and Beguinage -- Mysticism -- Joan of Arc: Saint or Heretic? -- Conclusion -- 6. Women on the Outskirts -- Crimes and Incarceration -- Sexual Transgressions.